Pembelajaran Matematika Dengan Strategi Writing In Perfomance Tasks (Wipt) Untuk Meningkatkan Kemampuan Menulis Matematis (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2010)
The problem of this paper is mathematical writing as a part of mathematical communication aspect that has not been developed optimally for the students. One of a teaching process to develop the students’ability in mathematical writing is Writing in Performance Tasks (WiPT) strategy. The main purpose of this paper is to investigate whether a teaching process using WiPT strategy can increase students’ability in mathematical writing. Key words: WiPT Strategy, mathematical writing, communication.